Penerapan Model Pembelajaran Kooperatif untuk Melatih Kreativitas Anak Kelompok B di TK Kartika II-1 Palembang - Pratiwi , Indah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to find out how the application of cooperative learning models to train thecreativity of group B children in TK Kartika II-1 Palembang, using qualitative research types ofcase study types. Data collection is done by observation, interviews, and documentation. Thesubject of the research was the application of the cooperative learning model to train thecreativity of children in group B Kartika II-1 Palembang. Interviews were conducted with TkKartika II-1 class teachers, for observation and documentation of the implementation of learning carried out in class B3 groups. Based on observations and discussions carried out so that it can be concluded that the application of cooperative learning models to train the creativity of children in group B Kartika II-1 Palembang has been going well. Because the implementation of activities carried out in accordance with the cooperative model and the learning process uses a scientific approach in accordance with the demands of the 2013 curriculum, the second steps of the cooperative learning model have been carried out according to established rules